2017
DOI: 10.12659/msm.900693
|View full text |Cite
|
Sign up to set email alerts
|

Serum Endocan as a Predictive Marker for Decreased Urine Volume in Peritoneal Dialysis Patients

Abstract: BackgroundEndocan is expressed in vascular endothelial cells, and its expression is enhanced following endothelial injury via inflammatory cytokines. Subsequently, endocan is secreted into the circulation. Thus, serum endocan levels are considered a marker of endothelial injury. However, to the best of our knowledge, no data on the serum endocan levels in peritoneal dialysis (PD) patients are available.Material/MethodsThis study included 21 PD patients who underwent peritoneal equilibration test (PET) more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Serum endocan levels were found higher in CKD patients than healthy subjects and in addition that serum endocan levels were found to be higher in CKD patients with CVD as compared to those without CVD [ 6 ]. In another study, serum endocan levels were observed higher in peritoneal dialysis patients than healthy subjects [ 24 ]. Raptis et al have reported higher serum endocan levels in ADPKD patients with eGFR 45-70 mL/min/1.73 m 2 than ADPKD patients with eGFR >70 mL/min/1.73 m 2 and higher serum endocan levels in ADPKD patients than controls [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum endocan levels were found higher in CKD patients than healthy subjects and in addition that serum endocan levels were found to be higher in CKD patients with CVD as compared to those without CVD [ 6 ]. In another study, serum endocan levels were observed higher in peritoneal dialysis patients than healthy subjects [ 24 ]. Raptis et al have reported higher serum endocan levels in ADPKD patients with eGFR 45-70 mL/min/1.73 m 2 than ADPKD patients with eGFR >70 mL/min/1.73 m 2 and higher serum endocan levels in ADPKD patients than controls [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, plasma and urinary endocan levels were significantly increased in kidney transplant patients with acute antibody-mediated rejection, and patients with high endocan levels showed worse renal survival [ 10 ]. In ESRD patients undergoing peritoneal dialysis, serum endocan levels have a predictive value for decreasing urine volume and showed a significant correlation with clinical characteristics and cardiovascular events [ 24 , 25 ]. However, only a few studies have evaluated endocan in hemodialysis patients [ 26 , 27 ], and the studies were conducted with a relatively small sample size, and did not analyze the association between clinical outcomes and endocan levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although no further analysis was conducted on this result, the following supposition can be made: given that patients in the lower endocan group have shorter hemodialysis (HD) duration than those in the higher endocan group, it is assumed that patients in the lower endocan group have a higher residual renal function. Previous studies reported that endocan levels showed a negative association with residual renal function [ 24 , 25 ]. The result of adding residual renal function to assess dialysis adequacy may differ from our prior result.…”
Section: Discussionmentioning
confidence: 99%
“…Whether endocan exerts pro-inflammatory or anti-inflammatory effects on the vascular endothelium remains to be determined. Regardless of its biological functions, plasma endocan has been shown to be correlated with inflammation severity and poor survival in various diseases, such as coronary artery disease, malignancy, chronic kidney disease, IgA nephropathy and sepsis 3745 .…”
Section: Discussionmentioning
confidence: 99%